Exclusive breastfeeding and child survival in children from 0 to 6 months of age in Peru: 2000, 2008 and 2014 - Yace-Martinez, Jessica (2019)
Objective: Determine whether compliance with exclusive breastfeeding is associated with child survival. Material and methods: Quantitative study, correlational with non-experimental design; The study population consisted of children from 0 to 6 months of age and their respective mothers in the periods 2000, 2008 and 2014, the data come from the Demographic and Family Health Survey (ENDES) of the periods 2000, 2008 and 2014, obtained from the INEI data repository. Child survival was defined as the absence of some form of malnutrition and anemia. Results: It was found that approximately 50.0% of children have an age of 0 to 3 months, 50.0% are of sex male, 60.0% comes from a full-term pregnancy, 90.0% had an adequate birth weight and approximately 70.0% did not use the bottle, 97.9% received exclusive breastfeeding in the 2000 period and approximately 63.0% received exclusive breastfeeding in the 2008 and 2014 periods, approximately 84.0% had child survival in the three study periods. Conclusion: There was no significant association between the fulfillment of exclusive breastfeeding and child survival in children from 0 to 6 months of age in Peru in the periods 2000, 2008 and 2014.